Peran Algoritma Media Sosial dalam Penyebaran Propaganda Politik Digital Menjelang Pemilu - Al Fatih, Ismail Zaky; Putera, Rachmatsah Adi; Umar, Zahri Hariman (Jurnal Kajian Stratejik Ketahanan Nasional, 2024)
Social media has transformed the political landscape, becoming crucial in general election preparations. It provides direct access to voters, a platform for political candidates to interact with audiences, and enables active participation in the political process. However, it also poses risks, such as the spread of false information, social division, and polarization. Algorithms on social media play a central role in shaping public perceptions of elections. These algorithms can create “filter bubbles,” where users are only exposed to views aligning with their beliefs, and “echo chambers,” reinforcing existing views. This qualitative research, using a literature study method, found that digital propaganda on social media influences public opinion, especially during elections. This propaganda employs hashtags, bots, fake accounts, rhetorical techniques, and emotional psychology. Hashtags can make conversations trending topics, while bots and fake accounts rapidly disseminate messages. To counteract the negative impacts of algorithms and digital propaganda, strict regulations, robust digital education, and literacy, and a comprehensive understanding of how algorithms work are essential. These measures are crucial to maintaining a democratic and inclusive political process during elections.